Meningkatkan Karakter Bangunan Bersejarah & Kenyamanan Visual dengan Pencahayaan Buatan Studi Kasus: Gedung London Sumatra Indonesia di Kota Medan - Harry Wibowo (Jurnal Indonesia Sosial Teknologi, 2021)
Medan City is famous for many historical buildings scattered all over the city. The building has a magnificent colonial architectural design. With the character of the building and its unique architectural details, this building is different from the others. But it is unfortunate that these buildings cannot be enjoyed at night. Due to the lack of artificial lighting received by the building. This study aims to obtain an overview of the visual comfort of the community, especially at night. The method used is a qualitative method to be able to understand the phenomena experienced by research subjects such as perception and by means of descriptions in the form of words and language, in a special natural context. Perceptions of the quality of building lighting are very much determined by the impression that comes out of a person at the time of seeing him, either directly or indirectly (using image media or computer screens). To facilitate the visual description of building lighting at night, modeling was carried out using Enscape software. The results of this study indicate that the visual quality of the building at night with the concept of good artificial planning (computer simulation) can improve the characteristics of the building, compared to using improvised lighting. With a good visual quality of the building, it will increase the various activities of the surrounding community and in the end it will make the historic building a regional spot at night.